2001
DOI: 10.1242/jcs.114.19.3445
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle roles for two 14-3-3 proteins duringDrosophiladevelopment

Abstract: Drosophila 14-3-3ε and 14-3-3ζ proteins have been shown to function in RAS/MAP kinase pathways that influence the differentiation of the adult eye and the embryo. Because 14-3-3 proteins have a conserved involvement in cell cycle checkpoints in other systems, we asked (1) whether Drosophila 14-3-3 proteins also function in cell cycle regulation, and (2) whether cell proliferation during Drosophila development has different requirements for the two 14-3-3 proteins. We find that antibody staining for 14-3-3 fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…As in the eye, we find that Tctp and 14-3-3 are required for the growth of the salivary gland. 14-3-3ε and 14-3-3ζ have redundant functions in imaginal discs [ 7 ], but have distinct roles in other tissues [ 9 , 28 ]. Our data show that 14-3-3ε, but not 14-3-3ζ, is essential for cell growth in salivary glands, providing additional evidence for isoform-specific functions of 14-3-3 proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the eye, we find that Tctp and 14-3-3 are required for the growth of the salivary gland. 14-3-3ε and 14-3-3ζ have redundant functions in imaginal discs [ 7 ], but have distinct roles in other tissues [ 9 , 28 ]. Our data show that 14-3-3ε, but not 14-3-3ζ, is essential for cell growth in salivary glands, providing additional evidence for isoform-specific functions of 14-3-3 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The main role of Foxo family proteins is to activate transcription [ 28 , 30 , 31 ]. However, our data show that the exogenous Foxo protein overexpressed in the salivary gland, which causes growth defects in the gland, is enriched in the cytoplasm (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…43 Similarly, the 14-3-3 protein has been implicated in the eye and the early neural development in Drosophila and mice. 44,45 On a different functional level, five of the detected pathways were also significant only in the eyed stage (Table 2). Again, the RAN pathway is involved in neural, brain and eye development.…”
Section: Resultsmentioning
confidence: 99%
“…Immunoblotting of the WCE and NE with anti-14-3-3β, γ, , σ, and ζ antibodies revealed that the total expression of all these isoforms was higher at the G 1 /S and G 2 /M phases of the cell cycle, particularly the expression of the σ and γ isoforms (Figure 5B). In addition to their role in cell signaling pathways, which would require the cytoplasmic presence of these proteins at all phases of the cell cycle, their role as check-point proteins (18,19,(45)(46)(47)(48)(49)(50)(51) may explain this increased expression. On the other hand, expression of the human replication origin binding protein, hOrc2p, whose expression and chromatin-bound state have been shown to be stable throughout the cell cycle (35), was approximately the same in both the WCE and the NE at all phases of the cell cycle (Figure 5B).…”
Section: Discussionmentioning
confidence: 99%